Thermal and suction effects on the anisotropic elastic shear moduli under various stress conditions - Bentil, Obed Takyi; Zhou, Chao (Indonesian Geotechnical Journal, 2025)
The elastic shear modulus of soils plays a pivotal role in assessing the serviceability of various geotechnical engineering infrastructures, particularly those subjected to fluctuating temperatures and suction levels. Despite its significance, the combined influence of temperature and suction on the elastic shear modulus remains inadequately explored. This study endeavours to improve the understanding of temperature and suction-dependent elastic shear modulus by employing an oedometer and an advanced triaxial apparatus capable of controlling temperature and suction, integrated with bender element probes and local strain measurement techniques. The investigation focuses on the anisotropic behaviour of the elastic modulus across a temperature range of 5 to 40ºC and suction values between 0 and 300 kPa under both saturated and unsaturated conditions. At the same temperature, the elastic shear modulus increases with an increase in suction, which is mainly attributed to stiffening effects of water meniscus with increasing suction. The results consistently indicate a decrease in the shear modulus after heating for all stress levels and suction conditions investigated. This heating-induced reduction can be attributed to several factors, including the reduction of interparticle forces and the decrease in air-water surface tension due to heating. Furthermore, the extent of the reduction in shear modulus depends upon the orientation of the shear plane, highlighting a significant change in the degree of anisotropy post-heating. This study sheds light on the complex interplay between temperature, suction, and the elastic shear modulus of soils and underscores the necessity for incorporating these coupled effects into the design and analysis of geotechnical structures under varying environmental conditions.